Constitucionalidade das medidas restritivas do direito fundamental à previdência social - Falcão, Marina Vasques Duarte de Barros (2012)
The subject of this thesis is an inquiry into an alternative to the time-related interpretation of social security law; one that fares beyond the plain protection of vested rights, perfect legal acts and res judicata. Regardless of the total fulfillment of the legal norm s application requirement, what is evaluated is the constitutional validity of a norm that restricts and retrogresses upon the right to social security. The latter is a fundamental right - both formally and materially, causing statutes that encroach on the legal protection offered by the General Social Security Regime to be subjected to the constitutional limits imposed on the legislator. Formal and material legitimacy are weighed, as per the explicit and implicit principles of the democratic and social state of law, adopted by the Brazilian constitutional order currently in force. In addition to the legality principle, this thesis dwells on the limits to the restrictions of the fundamental right to social security (the German Schranken- Schranken theory). This includes the legal certainty principle in its dual objective and subjective ramification, which entails the principle of legitimate citizen trust on government; the prohibition of social retrocession principle, with due regard to its suitability and the criticism that is due; the proportionality principle and its nature of a normative postulate; and, lastly, the ultimate fundamental right guarantee ensuing from the principle of the protection of a fundamental right s essential content